Anti-CRISPR-mediated continuous directed evolution of CRISPR-Cas9 in human cells - Andrew L. Sabol; Amanuella A. Mengiste; Prashant Singh; Vedagopuram Sreekanth; Samuel J. Hendel; Minh Thuan Nguyen Tran; Anton M. Barybin; Santosh Chaudhary; Ra’Mal M. Harris; Kristi E. Liivak; Zachary C. Severance; Cale M. Locicero; et al. (Proceedings of the National Academy of Sciences, 2026)
Engineering CRISPR-Cas systems for improved or altered function is critical to both research and therapeutic applications. Unfortunately, most optimization, especially directed evolution in bacterial hosts, fails to capture the functional requirements of the complex mammalian cellular milieu, where activity is usually required. Robust strategies to enable continuous directed evolution of genome-targeting agents directly in human cells remain lacking. Here, we introduce CRISPR-MACE (Mammalian cell-enabled Adenovirus-assisted Continuous Evolution) as a foundational technology to address this need. CRISPR-MACE integrates virus-based continuous evolution with anti-CRISPR-based tunable selection to generate Streptococcus pyogenes Cas9 variants with both increased and decreased DNA binding capacity and nearly 1,000-fold-enhanced resistance to AcrIIA4, the strongest known inhibitor of SpCas9. Notably, across independent evolution campaigns, the same Cas9 gatekeeper mutation reproducibly emerged first, enabling subsequent adaptive steps along two interdependent axes of Cas9 function. In addition to advancing CRISPR technologies, this work establishes key principles and synthetic circuits for continuously evolving CRISPR-Cas systems directly in human cells.